Analisa Perbandingan Kinerja Boiler Tanpa dan Dengan Menggunakan Glasswoll sebagai Isolator - Safri Gunawan; Supriadi; Hendra Susilo; Fadhlah Sinurat (Universitas Medan Area, 2022)
This study discusses the performance of boiler without and with insulation as a parameter that affects the performance of boiler. The purpose of this study is to compare the performance of boiler without using an insulator and with an insulator. The performance of the boiler is seen from the length of time reaches a boiling temperature at a pressure of 5 bar, the decrease in boiler temperature after reaching a pressure of 5 bar, and the duration of the boiler pressure reaching a pressure of 5 bar. The research method used was 14 liters of water and 4 kg of coconut shell. The first research was carried out without using insulation, furthermore it was continued by isolating the boiler using glasswool with the same conditions. The results obtained in boilers without and with glasswool insulation are very significant. Where the duration of boiling water is up to 41 minutes and 25 minutes, respectively. In addition, the final temperatures after 77 minutes and 118 minutes were 88.4 oC and 145 oC, respectively for boilers without and with insulators. The conclusion in this study states that the insulator greatly affects the performance of the boiler.